Safety of intensive care hyperbaric oxygen therapy sessions at a tertiary academic hospital - Aneta Miszewska; Jacek Kot; Ewa Lenkiewicz (Scientific Reports)
Abstract This study aimed to identify, based on available literature, the risk factors for adverse events during transport and hyperbaric oxygen therapy (HBOT) sessions in intensive care unit patients and to determine their impact on intra-ward mortality and hospitalization duration. A retrospective analysis was conducted on hospitalized intensive care patients requiring HBOT between 2013 and 2023 at the Department of Hyperbaric Medicine and Sea Rescue, University Centre for Maritime and Tropical Medicine in Gdynia, Poland. A total of 176 patients met the inclusion criteria for analysis. The following risk factors for adverse events during transport and HBOT sessions were identified: continuous intravenous infusions of catecholamines and analgo-sedation, nighttime HBOT sessions (56.55% of all sessions), presence of pleural cavity drainage, and mechanical ventilation via an intubation tube. The number of HBOT sessions had a statistically significant effect in reducing the risk of death (RR = 0.71, p < 0.001), while the administration of catecholamines significantly increased the risk of death (RR = 3.56, p = 0.045). Patients with severe infections (NSTI and gas gangrene) are at higher risk of adverse events and mortality. Therefore, every effort should be made to prevent untoward incidents during their HBOT sessions, including transport to the hyperbaric chamber. The first 72 h of hospitalization for critically ill patients receiving HBOT are crucial for intra-ward survival.